Applying an Ethical Framework to Herbal Medicine. (19th September 2018) - Chatfield, Kate; Salehi, Bahare; Sharifi-Rad, Javad; Afshar, Leila
Abstract : Herbal medicines make a vital contribution to healthcare globally, but from production through to practice, there are ethical challenges that require attention. Ethical challenges are often analysed through application of an ethical framework because this can facilitate a consistent and structured approach. In healthcare, the most commonly used framework over recent decades has been that of the four principles: beneficence, nonmaleficence, autonomy, and justice. However, for various reasons that are explained, this approach to ethical analysis is not the most fitting for the global phenomenon of herbal medicine. In this paper, a relatively new moral framework that is based upon the globally accepted values of care, respect, honesty, and fairness is explored in relation to herbal medicine for the first time. Through application of this framework, the ethical challenges and actions needed to address them become clear, thus resulting in practical recommendations for enhancing ethical standards in herbal medicine.